2016
DOI: 10.1007/s40119-016-0075-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Influence the Cardiovascular Benefits Observed with Sodium Glucose Co-Transporter-2 (SGLT-2) Inhibitors? A Meta-Regression Analysis

Abstract: IntroductionAlthough a large recent trial had shown improved cardiovascular outcomes of diabetic patients on sodium glucose co-transporter-2 (SGLT-2) inhibitors, the influence of gender differences on such outcomes is not known. Thus, we aimed to assess the impact of gender on such outcomes in the patients with type 2 diabetes mellitus receiving SGLT-2 inhibitors.MethodsA search of electronic databases was conducted for all randomized trials comparing SGLT-2 inhibitors with placebo in patients with diabetes me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Since differences including cardiovascular results between men and women have been reported for some SGLT-2 inhibitors, it is necessary to explore sex-associated differences in the effects of DWP16001 in further studies. 38,39 Nevertheless, since there were similarities in the PD response between healthy subjects and patients for other SGLT-2 inhibitors, the results of this study are thought to provide meaningful information for clinical use. Oropharyngeal pain 3 (37.50) Oropharyngeal pain 1 (12.50) 1 Chest discomfort 1 (12.50) 1 Chest pain 1 (12.50) 1 Chills 1 (9.09) 1 Cold sweat 1 (12.50) 1 1 (12.50) 1 Dysuria 1 (12.50) 1 Urinary retention 1 (12.50) 1 Balanoposthitis 1 (12.50) 1 All data presented as number of subjects (percentage of subjects) number of events.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Since differences including cardiovascular results between men and women have been reported for some SGLT-2 inhibitors, it is necessary to explore sex-associated differences in the effects of DWP16001 in further studies. 38,39 Nevertheless, since there were similarities in the PD response between healthy subjects and patients for other SGLT-2 inhibitors, the results of this study are thought to provide meaningful information for clinical use. Oropharyngeal pain 3 (37.50) Oropharyngeal pain 1 (12.50) 1 Chest discomfort 1 (12.50) 1 Chest pain 1 (12.50) 1 Chills 1 (9.09) 1 Cold sweat 1 (12.50) 1 1 (12.50) 1 Dysuria 1 (12.50) 1 Urinary retention 1 (12.50) 1 Balanoposthitis 1 (12.50) 1 All data presented as number of subjects (percentage of subjects) number of events.…”
Section: Discussionmentioning
confidence: 90%
“…Because a relatively small number of healthy male subjects participated, information on the AEs of DWP16001 was limited. Since differences including cardiovascular results between men and women have been reported for some SGLT‐2 inhibitors, it is necessary to explore sex‐associated differences in the effects of DWP16001 in further studies 38,39 . Nevertheless, since there were similarities in the PD response between healthy subjects and patients for other SGLT‐2 inhibitors, the results of this study are thought to provide meaningful information for clinical use.…”
Section: Discussionmentioning
confidence: 91%
“… 2 A 2016 meta-analysis of 26 SGLT-2i trials demonstrated a relatively smaller reduction in cardiovascular mortality when the proportion of women enrolled in the trials increased. 3 In addition to sex-based differences in efficacy, women experience a higher proportion of some drug-related adverse events with SGLT2i (primarily genital and urinary infections) compared with men. 4 , 5 Sex-specific differences in efficacy have also been reported with GLP1-RAs, namely, a larger relative reduction in cardiovascular events in women compared with men, 6 but more frequent adverse events (particularly gastrointestinal events).…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to explore the sex‐associated differences in the effects of DWP in further studies, as differences in PD (i.e. cardiovascular results) between men and women were reported for some SGLT‐2 inhibitors 24,25 . Second, drug interactions were explored in healthy subjects in this study.…”
Section: Discussionmentioning
confidence: 99%